Analytical study of Offensive Tactic Performance of Some Iraqi League Clubs season 2016 – 2017 First Stage Soccer - Lazim, Asaad (Journal of Physical Education, 2017)
The importance of the research lies in the importance of offensive performance in the variables selected by the experts and specialist in soccer (direct free kick, corner kick, scoring, outside penalty area, passing). The problem of the research lies in the weakness of primer league's offensive performance. The researcher conducted interviews with many experts in this field to pinpoint the variables that led to this weakness in offensive performance during the matches. The research aimed at identifying the level of offensive performance for Iraqi primer league clubs as well as comparing the levels of offensive performance among clubs. The researcher used the descriptive method. The subjects were Iraqi primer league soccer clubs. The results showed a great weakness in some offensive aspects understudy. Finally the researcher recommended establishing an analytical committee for the league that focuses on game change, short passes, inter – passes.